Respiratory syncytial virus (RSV) disease - new data needed to guide future policy - Louis Bont; Harish Nair (Edinburgh University Global Health Society, 2015)
RSV is the main cause of childhood lower respiratory infections, globally, an important cause of childhood wheeze and may be responsible for a substantial burden of disease in the very elderly and in adults with chronic medical problems, such as COPD. It is thus responsible for substantial healthcare and social costs. There are currently many companies and academic groups developing and testing candidate vaccines and there is an expectation that these will lead to effective and safe vaccines which will be available to health systems globally in the short- medium term. Despite this, there is an incomplete understanding of RSV disease, especially in adult groups, and large scale data are only available from a few countries and settings leading to low levels of awareness of the importance of this pathogen. We discuss the need for widespread national sentinel systems of RSV surveillance and some means by which this could be achieved. These data will be needed by national policy makers and immunisation advisory groups to guide future priority setting and decision making.